2008
DOI: 10.1007/s11745-008-3152-y
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Lipid Composition Plays a Central Role in the Maintenance of Epithelial Cell Adhesion to the Extracellular Matrix

Abstract: Focal contacts (FC) are membrane-associated multi-protein complexes that mediate cell-extracellular matrix (ECM) adhesion. FC complexes are inserted in detergent-resistant membrane microdomains enriched in phosphatidylinositol-4,5-bisphosphate (PtdIns(4,5)P2); however, the influence of membrane lipid composition in the preservation of FC structures has not been extensively addressed. In the present work, we studied the contribution of membrane lipids to the preservation of renal epithelial cell adhesion struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
19
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…By using a two-step centrifugation procedure and changing sucrose concentration, Triton X-100 resistant membrane microdomains from the microsomal fraction of primary cultured collecting duct cells were isolated, where FA complexes are located. 17 In such DRM, it has been found that vinculin and talin are bound to PI(4,5)P 2 and that both proteins interact, as assessed by immunoprecipitation analysis. The presence of vinculin bound to PI(4,5)P 2 , together with talinvinculin association in DRM, constitutes the biochemical expression of the existence of FA complexes in DRM isolated from rat renal papillae.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…By using a two-step centrifugation procedure and changing sucrose concentration, Triton X-100 resistant membrane microdomains from the microsomal fraction of primary cultured collecting duct cells were isolated, where FA complexes are located. 17 In such DRM, it has been found that vinculin and talin are bound to PI(4,5)P 2 and that both proteins interact, as assessed by immunoprecipitation analysis. The presence of vinculin bound to PI(4,5)P 2 , together with talinvinculin association in DRM, constitutes the biochemical expression of the existence of FA complexes in DRM isolated from rat renal papillae.…”
mentioning
confidence: 99%
“…The presence of vinculin bound to PI(4,5)P 2 , together with talinvinculin association in DRM, constitutes the biochemical expression of the existence of FA complexes in DRM isolated from rat renal papillae. 17 Once established that FA complexes were located in DRM, the DRM lipid composition was characterized in comparison with the Triton X-100 soluble fractions. 17 Cholesterol concentration was ten times higher in DRM than in the Triton X-100 soluble fraction.…”
mentioning
confidence: 99%
See 3 more Smart Citations